2013
DOI: 10.1161/circinterventions.113.000220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Procedural Characteristics Associated With Higher Radiation Exposure During Percutaneous Coronary Interventions and Coronary Angiography

Abstract: Background-We aim to study the clinical and procedural characteristics associated with higher radiation exposure in patients undergoing percutaneous coronary interventions (PCIs) and coronary angiography. .001) were associated with the highest radiation exposure. After adjusting for procedural complexity, radial access route was not associated with increased radiation exposure (β=1.00; CI, 0.98-1.03; P=0.67). Conclusions-In the largest study population to assess radiation exposure, we found that high body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 13 publications
(17 reference statements)
0
41
1
Order By: Relevance
“…The evidence for this remains controversial, and more recent studies have suggested that there is no difference in radiation exposure between radial and femoral cases, when performed by experienced radial operators [17]. Although fluoroscopy time and radiation dose were both numerically higher in the transradial group, we did not find a statistically significant difference in fluoroscopy time or radiation dose between the two groups.…”
Section: Discussioncontrasting
confidence: 85%
“…The evidence for this remains controversial, and more recent studies have suggested that there is no difference in radiation exposure between radial and femoral cases, when performed by experienced radial operators [17]. Although fluoroscopy time and radiation dose were both numerically higher in the transradial group, we did not find a statistically significant difference in fluoroscopy time or radiation dose between the two groups.…”
Section: Discussioncontrasting
confidence: 85%
“…Furthermore, the predictors of radiation exposure remain far more complex than simply the access site alone. Indeed, recent analyses have suggested that increasing body mass index, history of coronary artery bypass grafting, increasing number of treated lesions, and chronic‐total occlusions were associated with increased radiation exposure . Others invoke patient sex, lesion complexity, lesion location, and the performing physician as also contributing to subsequent radiation exposure .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, minimizing both patient and the catheterization staffs’ radiation exposure remains a priority. The TR approach is assumed to result in a higher radiation exposure than its TF equivalent, but this continues to be the subject of considerable debate . As the TR approach becomes more commonly adopted, so too do concerns over a subsequent risk of increased radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary angiography in patients with CABG not only lasts longer, but also leads to higher irradiation and nephrotoxicity than coronary angiography in patients without CABG . In addition, the CABG population is certainly more fragile and at a higher risk of complications related to more comorbidities, such as polyvascular diseases, elderly, overweight, and kidney failure.…”
Section: Discussionmentioning
confidence: 99%